A legal analysis of the application of corporate governance principles in the local government sphere as a measure to improve service delivery - Mokgopo, Tshehledi Isaac (My University, 2017)
The new democratic government of South Africa came into power in 1994 and it inherited a dysfunctional municipalities. In fact it inherited a country with high levels of poverty, growing levels of inequality and also social dysfunctionality. The local government sphere was established in South Africa with the main aim of addressing inequality, segregation, inequity, discrimination in the provision of municipal services and eradication poverty within communities. However, ever since the establishment of local government sphere in South Africa, the sphere of local government is fraught with many challenges which make it impossible for municipalities to render proper municipal services to the members of the public. This is evident from the protests which were observed in the country ever since the year 2008 were communities demanded better services from their municipalities. This mini-dissertation therefore discusses the application of the principles of corporate governance in delivering and improving municipal service in South Africa. It further discusses the legislative framework and the institution of government which are responsible for the effective implementation of corporate governance in the local government sphere. Pursuant to that it also explains the concept of Corporate Governance within the local government. Furthermore, it discusses the parameters of the challenges that are faced by the municipalities which are ranging from fraud, nepotism, corruption and poor financial management which result in poor service delivery.
Thesis (M. Dev.) -- University of LImpopo, 2017.
Keywords: Dysfunctional municipalities; Poverty; Service delivery; Poor financial management; Municipal services -- Law and legislation -- South Africa